PENGARUH INOVASI DAN KREATIVITAS PROGRAM PEMASARAN TERHADAP KINERJA PEMASARAN YANG DIMEDIASI OLEH KAPABILITAS JEJARING USAHA (STUDI PADA KELOMPOK WIRAUSAHA PEMUDA (KWP) BINAAN DINAS PEMUDA DAN OLAH RAGA PROVINSI JAWA TENGAH) - Purdianto, 1342020009 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study examines the effect of innovation and creativity influence marketing to performance marketing program mediated by a business networking capabilities. This research was conducted Youth Entrepreneurial Group (KWP) Patronage Department of Youth and Sports in Central Java province with the sample used in the study amounted to 104 respondents. Engineering test data used in this study include testing the validity of the factor analysis, Cronbach alpha reliability test, multiple regression analysis, and t test and the coefficient of determination to prove the truth of the hypothesis. Statistical analysis showed that the results of F test with a significance value of 0.000, which means that innovation, creative marketing programs and business networking capabilities are the right variables / feasible to explain variations in performance variables of marketing. The test results influence between the variables with t test showed that the innovation and creativity of marketing programs proven significant positive effect on the business networking capability and innovation, creative marketing programs and business networking capabilities proved positive and significant impact on the performance of marketing. Can also be shown that the coefficient of determination of test variables of innovation, creative marketing programs and business networking capabilities of the performance marketing has a coefficient of determination of 0.616 or 61.6%. This means that the variables of innovation, creative marketing programs and business networking capabilities together have contributed 61.6% to the marketing performance. While the remaining 38.4% is influenced by other variables not included in this study. From the test results of mediation can be proved that the business networking capability is not a mediating variables that can explain the effect of indirectly from the innovation and creativity of the marketing program for marketing performance. Keywords:       innovation, creative marketing programs, business networking capabilities, performance marketing